Relação entre estrutura e função muscular de membros superiores em pacientes com doença pulmonar obstrutiva crônica - Souza, Leandra Marques de (2011)
Chronic obstructive pulmonary disease (COPD) is a preventable and treatable disease characterized by airflow limitation that is not fully reversible. COPD is also characterized by exercise intolerance which can be caused by multiple factors. Quadriceps femoris is the most commonly muscle studied in skeletal muscle dysfunction syndrome in COPD. However, it has been speculated a regional distribution of muscle weakness preserving diaphragm, abdominal muscles and muscles of the upper limbs (UL). It is unclear whether the loss of strength is proportional or not to the reduced muscle mass ("quantitative" or "qualitative" aspects, respectively) in UL of patients with COPD, as well as the structure (strength) is a determinant of UL aerobic capacity. The aim of this study was to investigate the relationships between structure (muscle mass) and function (strength and local endurance, maximal aerobic capacity and exercise tolerance) of the peripheral muscles of UL in patients with COPD. Thirteen COPD patients and 6 controls were evaluated for UL maximal incremental test, maximal voluntary contraction of the biceps and triceps and anthropometric measurements. The main results were (i) patients with COPD had lower ventilatory reserve at maximal test on UL cycle ergometer (ii) there was a relationship between the local structure (muscle mass) and systemic performance (aerobic capacity, ventilatory demand and respiratory muscle strength) and (iii) it was observed relationship between system structure and several functional attributes of system performance and aerobic capacity. In conclusion, muscle mass is crucial in systemic attributes, ie, aerobic capacity and maximum workload, but not the local attributes (strength and endurance).